Using additive indices and principal components to select sexual genitors and hybrids of Urochloa decumbens - Matias, Filipe Inacio; Valle, Cacilda Borges do; Gouveia, Beatriz Tome; Moro, Gustavo Vitti [UNESP]; Lima Barrios, Sanzio Carvalho (Brazilian Soc Plant Breeding, 2020)
The selection of sexual genitors in Urochloa decumbens breeding is dependent upon the performance of their progeny for several traits simultaneously. Thus, our objectives were to (i) compare the efficiency of indices to select genitors of U. decumbens, (ii) evaluate the genetic gains obtained through selection intensities, and (iii) evaluate the multivariate pattern of progenies through principal components analysis (PCA). For this purpose, 1415 hybrids from 75 progenies of full siblings were evaluated at Embrapa Beef Cattle (Brazil) using seven cuts for dry matter production, regrowth, protein, fiber, lignin, and percentage digestibility. Statistical analyses were performed using mixed models and PCA. The direct selection for dry matter production provided a 37.51% genetic gain. Agronomic traits using indices provided greater gains. Genitors selected using PCA Biplot were similar to selections using indices. Indices and PCA were proven to be an excellent tool to select multi-traits in U. decumbens.
Keywords: Brachiaria decumbens; genetic gain; recurrent selection; tropical forage